Neuropathological effects of persistent infection of mice by mouse hepatitis virus. - Virelizier, J L (1975)
Mouse hepatitis virus (MHV3) can persist for months in strains of mice with genetically controlled "semisusceptibility" to this virus. The pathology of the chronic neurological disease induced in these animals has been investigated by conventional histology and immunofluorescence. A2G mice develop a chronic choroidoependymitis and meningitis leading to severe hydrocephalus and hydromyelia. In C3H mice a widespread vasculitis was observed, with both viral antigens and bound immunoglobulins in vessal walls. No significant glomerulonephritis was found. Systemic amyloidosis was present in the spleen, liver, and kidneys. The virus was not detected in neural tissues, but brain and spinal cord lesions were found near inflammatory areas surrounding damaged vessels. It is suggested that viral persistance in ependymal cells is directly responsible for the lesions in A2G mice, whereas an immunopathological lesion of blood vessels of the central nervous system underlines the damage to mice of the C3H strain.